Perioperative Management of Craniotomy for Cerebral Clipping Aneurysm with Intraoperative Neurophysiological Monitoring: A Case Report - Muhammad Remo Lingga Riesta Armyda; Hamzah Hamzah; Dhania Anindita Santosa; Kakung Muhamamad Yusuf; Zakaria Zakaria (Jurnal Neuroanestesi Indonesia, 2026)
Introduction: The incidence of subarachnoid hemorrhage (SAH) is approximately 9 per 100,000 population per year. SAH caused by ruptured brain aneurysm accounts for around 80% of non-traumatic events, followed by 10% perimesencephalic hemorrhage and another 10% due to arteriovenous malformation (AVM). Case: A 50-year-old female patient weighing 50 kg who presented on post-ictus day 14 with aneurysmal subarachnoid hemorrhage secondary to a ruptured middle cerebral artery (MCA) aneurysm with GCS 14 (E4V4M6) without any neurological deficit with WFNS grade II. Discussion: The patient underwent craniotomy and aneurysm clipping performed by a vascular neurosurgeon. A lumbar drain was inserted preoperatively to facilitate controlled cerebrospinal fluid (CSF) drainage and promote intraoperative brain relaxation. During aneurysm clipping, intraoperative neurophysiological monitoring (IONM) was performed by a neurophysiologist to continuously assess motor evoked potentials (MEPs) and somatosensory evoked potentials (SSEPs), ensuring the preservation of neural pathway integrity throughout the procedure. Conclusion: The primary goal of anesthetic management was to prevent elevations in intracranial pressure (ICP) and carefully control mean arterial pressure (MAP) before vessel occlusion and throughout aneurysm clipping to maintain an optimal balance between cerebral perfusion pressure (CPP) and transmural pressure (TMP). Neuroanesthesia plays an important role in the perioperative management of patients from the initial stabilization in the emergency department, intraoperative neuroprotective strategies during surgical intervention, and postoperative care in the neurologic intensive care unit.